Rollator use adversely impacts on assessment of gait and mobility during geriatric rehabilitation - Schwenk, Michael; Schmidt, Marita; Pfisterer, Mathias Hans-Dieter; Oster, Peter; Hauer, Klaus (Journal of rehabilitation medicine, 2011)
Objective: To investigate the influence of the use of a rollator walking aid on assessment of gait a...
Gesehen am 28.10.2022